Graphene‐Based Femtogram‐Level Sensitive Molecularly Imprinted Polymer of SARS‐CoV‐2. Issue 24 (14th November 2021) - Hashemi, Seyyed Alireza; Bahrani, Sonia; Mousavi, Seyyed Mojtaba; Omidifar, Navid; Behbahan, Nader Ghaleh Golab; Arjmand, Mohammad; Ramakrishna, Seeram; Lankarani, Kamran Bagheri; Moghadami, Mohsen; Firoozsani, Mohammad
Abstract: Rapid distribution of viral‐induced diseases and weaknesses of common diagnostic platforms for accurate and sensitive identification of infected people raises an urgent demand for the design and fabrication of biosensors capable of early detection of viral biomarkers with high specificity. Accordingly, molecularly imprinted polymers (MIPs) as artificial antibodies prove to be an ideal preliminary detection platform for specific identification of target templates, with superior sensitivity and detection limit (DL). MIPs detect the target template with the "lock and key" mechanism, the same as natural monoclonal antibodies, and present ideal stability at ambient temperature, which improves their practicality for real applications. Herein, a 2D MIP platform consisting of decorated graphene oxide with the interconnected complex of polypyrrole‐boronic acid is developed that can detect the trace of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) antigen in aquatic biological samples with ultrahigh sensitivity/specificity with DL of 0.326 and 11.32 fg mL –1 using voltammetric and amperometric assays, respectively. Additionally, the developed MIP shows remarkable stability, selectivity, and accuracy toward detecting the target template, which paves the way for developing ultraspecific and prompt screening diagnostic configurations capable of detecting the antigen in 1 min or 20 s using voltammetric or amperometric techniques. Abstract : A molecularly imprinted polymer as an artificial monoclonal IgG antibody is developed for prompt, accurate, sensitive, and specific detection of betacoronaviruses, i.e., severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), in various biological and non‐biological media. The as‐developed configuration shows femtogram‐level detection limit and only reacts with its imprinted template via "lock and key" mechanism the same as a natural monoclonal antibody.